Europium nanosphere-based fluorescence strip sensor for ultrasensitive and quantitative determination of fumonisin B1. Issue 43 (21st October 2020) - Guo, Lingling; Wang, Zhongxing; Xu, Xinxin; Xu, Liguang; Kuang, Hua; Xiao, Jing; Xu, Chuanlai
Abstract : The developed time-resolved fluorescence immunochromatographic assay can be widely applicable as an ultrasensitive, rapid detection method for FB1 in grains. Abstract : Contamination of grains and related products by fumonisins (FBs) is increasingly becoming a serious food security issue. The aim of this work was to develop a europium fluorescent microsphere-based time-resolved fluorescence immunochromatographic assay (TRFICA) for FB1 detection in different grains, including corn, corn flour, wheat, rice and brown rice. Standard curves for the five types of grain matrix were established, and showed good linearity ( R 2 > 0.975), LOD of 8.26 μg kg −1, and a wide working range of 13.81–1000 μg kg −1 . The recoveries of TRFICA for FB1 detection ranged from 82.85–103.62% with variation coefficients of 1.92–15.33%. Two corn reference materials and other natural samples were tested using TRFICA. The same samples analyzed by liquid chromatography tandem mass spectrometry further confirmed the TRFICA results. The entire detection time of TRFICA was within 30 min. Thus, this developed TRFICA can be used for onsite detection and quantitation of FB1 in grains.